UJI PEMBERIAN LIMBAH PADAT PABRIK KOPI DAN URINE KAMBING TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum Mill) - Sulardi (Universitas Pembangunan Panca Budi, 2018)
Organic fertilizers can be made by utilizing organic waste through the process of decomposition by microorganisms and the metabolic remains of living things, one of which is the making of organic fertilizer by utilizing solid waste of coffee plants and goat urine. This study aims to determine the interaction of giving coffee plant solid waste and goat urine to the growth and production of tomato plants (Lycopersicum esculentum Mill). This research method uses factorial randomized block design with 2 treatments. The treatment factor consisted of giving coffee plant solid waste (K) with 4 levels, namely: K0 = 0 (Control), K1 = 300g / polybag, K2 = 600g / polybag, K3 = 900g / polybag. The treatment factor consisted of giving Goat Urine (U) with 4 levels, namely: U0 = 0 (Control), U1 = Liquid organic fertilizer (20 ml / polybag), U2 = Liquid organic fertilizer (40 ml / polybag), U3 = Fertilizer organic liquid (60 ml / polybag). The parameters observed in this study were plant height aged 2, 4 and 8 MST, number of fruits per sample and number of fruits per plot. The results showed the effect of giving coffee plant solid waste to the growth and production of tomato plants (Lycopersicum esculentum Mill) had a very significant effect on plant height aged 2, 4, 6 and 8 MST, but the effect was not significant on the number of fruits per sample and number of fruit per plot . The administration of goat urine coffee waste to the growth and production of tomato plants (Lycopersicum esculentum Mill) had no significant effect on plant height aged 2, 4, and 8 MST, number of fruits per sample and number of fruit per plot. The interaction of giving coffee skin waste and goat urine to the growth and production of tomato plants (Lycopersicum esculentum Mill) has no significant effect on all parameters.